Penyelasaian Permasalahan Hukum Islam Secara Yuridis dan Diplomatis (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
Resolving Islamic legal issues can be done through a legal and diplomatic approach. The legal approach refers to the formal legal system, such as religious courts and religious scholars' fatwas, which prioritize legal certainty based on the sources of Islamic law, namely the Qur'an, Sunnah, Ijma', and Qiyas. Meanwhile, the diplomatic approach emphasizes more on deliberation, mediation, and negotiation in order to achieve a peaceful solution that remains based on the principles of Islamic law. The combination of these two approaches can create a resolution mechanism that is more effective, fair, and in accordance with the needs of the Muslim community. The research method applied in writing this journal is a qualitative research method with a descriptive-analytical approach. This study describes how the resolution of Islamic law is carried out legally and diplomatically and analyzes the effectiveness of each method in practice. Research data were collected through a literature study of Islamic legal sources, religious court regulations, and cases of Islamic legal settlement. The results of the study indicate that the legal approach is more effective in providing legal certainty and protection of individual rights, while the diplomatic approach is more flexible in maintaining social harmony and avoiding prolonged conflict. Therefore, integration between these two approaches is very necessary in resolving Islamic legal issues more comprehensively and fairly.